Current History and National Affairs of Nepal - Ojha, Meena (Historical Journal, 2020)
One can find chains of people's struggle for freedom nationality, national, unity, integrity and democracy for centuries past when studies and researches carried out into the History of Nepal. People's participation in such struggles can't be exaggerated as the people themselves are the creators of the history. Because of apathy, insincere activities, inability, unclearity in vision and objective of political leadership, economic development and task of building new Nepal always remained limited only in speech and futile ambition.